2014
DOI: 10.4103/2249-4863.130263
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practices towards medical research amongst the postgraduate students of pravara institute of medical sciences university of central India

Abstract: Background:Health research training is an essential component of medical education and a vital exercise to help develop physician research skills.Objectives:This study was carried out to assess the knowledge, attitude, and practices towards health research amongst the postgraduate students of Pravara Institute of Medical Sciences University of central India.Materials and Methods:A cross-sectional study was carried out from August to October 2012. A total of 116 postgraduate students were interviewed. Knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 6 publications
20
36
1
Order By: Relevance
“…Lesser number of participants (36.8%) knew the definition of research hypothesis. This was in accordance with the studies done by Giri et al, 11 Rani and Priya, 12 and Sharma et al, 13 while another study done by Pawar et al 9 showed higher number of participants (58.0%) knew the definition of research hypothesis. In the present study, majority of participants (64.7%) did not know the full form of MEDLINE.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Lesser number of participants (36.8%) knew the definition of research hypothesis. This was in accordance with the studies done by Giri et al, 11 Rani and Priya, 12 and Sharma et al, 13 while another study done by Pawar et al 9 showed higher number of participants (58.0%) knew the definition of research hypothesis. In the present study, majority of participants (64.7%) did not know the full form of MEDLINE.…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, higher number of participants (63.9%) did not knew the full form of MEDLARS. This was in accordance with the study done by Giri et al 11 where 82.0% participants did not knew the full form of MEDLARS. Our study revealed majority of participants, i.e., 70.7%, did not know from whom to seek approval for conducting clinical research using new drugs in India.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17][18][19] Studies on chiropractic students' attitudes specifically have also been done. For example, Newell and Cunliffe 19 conducted such a study on undergraduate students at McTimoney Chiropractic College and found that 64% of their 119 student respondents found research interesting, 54% thought it was difficult, and 75% considered chiropractic research to be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Bio-Medical research is a systemic collection, analysis and interpretation of data with its critical appraisal, used by physicians for establishing the scientific basis for treatment of patients and imparting evidence-based clinical care 1,2 . It is a pivotal tool in amelioration of medical science.…”
Section: Introductionmentioning
confidence: 99%